Boost. Asio C++ network programming : learn effective C++ network programming with Boost. Asio and become a proficient C++ network programmer - Anggoro, Wisnu; Torjo, John (Community experience distilled., 2015)
Learn effective C++ network programming with Boost. Asio and become a proficient C++ network programmer About This Book Learn efficient C++ network programming with minimum coding using Boost. Asio Your one-stop destination to everything related to the Boost. Asio library Explore the fundamentals of networking to choose designs with more examples, and learn the basics of Boost. Asio Who This Book Is For This book is for C++ Network programmers with basic knowledge of network programming, but no knowledge of how to use Boost. Asio for network programming. What You Will Learn Prepare the tools to simplify network programming in C++ using Boost. Asio Explore the networking concepts of IP addressing, TCP/IP ports and protocols, and LAN topologies Get acquainted with the usage of the Boost libraries Get to know more about the content of Boost. Asio network programming and Asynchronous programming Establish communication between client and server by creating client-server application Understand the various functions inside Boost. Asio C++ libraries to delve into network programming Discover how to debug and run the code successfully In Detail Boost. Asio is a C++ library used for network programming operations. Organizations use Boost because of its productivity. Use of these high-quality libraries speed up initial development, result in fewer bugs, reduce reinvention-of-the-wheel, and cut long-term maintenance costs. Using Boost libraries gives an organization a head start in adopting new technologies. This book will teach you C++ Network programming using synchronous and asynchronous operations in Boost. Asio with minimum code, along with the fundamentals of Boost, server-client applications, debugging, and more. You will begin by preparing and setting up the required tools to simplify your network programming in C++ with Boost. Asio. Then you will learn about the basic concepts in networking such as IP addressing, TCP/IP protocols, and LAN with its topologies. This will be followed by an overview of the Boost libraries and their usage. Next you will get to know more about Boost. Asio and its concepts related to network programming. We will then go on to create a client-server application, helping you to understand the networking concepts. Moving on, you will discover how to use all the functions inside the Boost. Asio C++ libraries. Lastly, you will understand how to debug the code if there are errors found and will run the code successfully. Style and approa ...